Hubungan Tingkat Pengetahuan Ibu Dengan Penerapan Inisiasi Menyusui Dini (IMD) Di Klinik Semarang - Komsiyah Komsiyah; Dwi Indarti; Millenia Ekatania (Indonesian Journal of Nursing Research (IJNR), 2020)
Early Breastfeeding Initiation (IMD) is the process of breastfeeding the baby immediately after the baby is born, where the baby is left looking for the mother's own nipples. IMD is very important not only for the baby, but also for the mother. impact on the higher infant mortality rate (IMR). The purpose of this study analyze the relationship between mother's level of knowledge and the implementation of Early Breastfeeding Initiation (IMD). This type of research is a quantitative descriptive study with a cross-sectional study approach. A sample of 32 respondents using total sampling techniques in accordance with inclusion and exclusion criteria. The study was conducted at the Semarang Clinic on May 20 - June 20, 2020. The relationship between mother's level of knowledge and the implementation of Early Breastfeeding Initiation (IMD) with a value of p (0,000) <0.05. Early Breastfeeding Initiation (IMD) provides many benefits for the health of mothers and newborns. Benefits for mothers Early breastfeeding initiation (IMD) has been shown to increase the level of the hormone oxytocin and accelerate uterine involution 2 hours post partum and shorten the time of placental release so as to prevent post partum hemorrhage which is one of the biggest causes of maternal death throughout the world including Indonesia. Benefits for babies, touching with the mother provides warmth, calmness so that breathing and baby's heartbeat becomes regular. If IMD is not done immediately, it will have an impact on the higher IMR in Indonesia. Therefore it can be concluded that there is a significant relationship between the level of knowledge of the mother with the implementation of the Early Breastfeeding Initiation (IMD).Key words: Mother's KnowledgeEarly Breastfeeding Initiation